Metode Project Based Learning dalam Pembelajaran Bahasa Arab Perspektif Psikolinguistik - Novita Maula Salsabila; Setiyawan, Agung (Journal of Arabic Education and Linguistic, 2024)
Often in the learning process, teachers and students face various obstacles that hinder the effective achievement of learning objectives. Determining the appropriate method is a key factor in achieving learning objectives. One of the learning approaches currently attracting attention is Project-Based Learning (PjBL). This research aims to identify the effectiveness of Project-Based Learning (PjBL) in the Arabic language learning process from a psycholinguistic perspective. This study is a literature review where data is obtained from books, articles, and related literature. After data processing, analysis proceeds through three stages: data reduction, data presentation, and drawing conclusions. PjBL method is project-oriented and considered effective in cognitive, affective, and psychomotor aspects. Psycholinguistics in Arabic language learning cannot be ignored. The application of PjBL from a psycholinguistic perspective shows effectiveness in language acquisition, especially in Arabic language.